The environmental impact of vehicle circulation tax reform in Germany - Christiane Malina (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2016)
A core political strategy for reducing greenhouse gas emissions from road transportation in Germany is to incentivize the purchase of motor vehicles with relatively low tailpipe CO2 emissions. Consequently, since mid-2009, owners of new cars in Germany face an annual vehicle circulation tax that is partially levied according to vehicles' CO2 emission index. In this paper, I estimate the effect of CO2 -based vehicle circulation taxation in Germany on annual CO2 combustion emissions from passenger cars and CO2 climate costs using a nested logit approach on a novel panel-dataset containing registration, cost and vehicle characteristic information on approximately 7,000 unique vehicle models and approximately 19.5 million new vehicle registrations in Germany from 2007 to 2013. This approach first yields vehicle model specific estimates for the elasticity of new vehicle registrations with regard to the circulation tax. These elasticities are used to estimate changes in new vehicle registrations by model, which are then combined with model-specific CO2 emission factors and segment-specific annual distances driven to yield total emission changes attributable to the change in vehicle circulation tax. Finally, physical changes in emissions are converted into changes in monetary climate damages. Uncertainty in the elasticity of new vehicle registrations by segment with regard to vehicle circulation tax, the fuel economy and corresponding CO2 emission indices of vehicles, distances traveled by market segment, and in the monetary damages resulting from CO2 emissions are propagated through the analysis. Overall I find statistically significant, but relatively small reductions in CO2 emissions and climate costs due to the change in taxation: When simulating the ceteris paribus effect of the most stringent taxation regime implemented in 2014 on the pre-tax change models available in 2008, median registrations are estimated to decrease by approx. 9,500 vehicles, or 0.3 per cent of total new registrations. In addition, changes in registrations of individual vehicle models within each market segment lead to a relatively small reduction of segment- specific CO2 emission indices (0.03 to 0.1 per cent across segments). The reduction in new registrations and reduction in CO2 emission indices decrease median CO2 combustion emissions from newly registered vehicles by 35,000 t (90 per cent confidence interval: 31.000 to 39.000 t), and climate costs by exteuro 1.1 Million (90 per cent confidence interval: exteuro 0.1 to 2.2 Million), or 0.4 per cent of total CO2 emissions and climate costs from newly registered cars.
Keywords: 330; vehicle circulation tax; road transportation; climate costs; nested logit model